Управління розвитком промислового підприємства в контексті зниження трансакційних витрат - Гавкалова, Н. Л.; Власенко, Т. А. (НТУ "ХПІ", 2014)
У статті досліджено понятійно-категоріальний апарат теорії трансакційних витрат в контексті функціонування виробничої діяльності підприємств Проаналізовано трактування поняття трансакційних витрат, що були розроблені в рамках неоінституційної теорії. Розглянуто фактори зовнішнього та внутрішнього середовища підприємства. Обґрунтовано необхідність впровадження новітніх методів розвитку підприємства для зниження рівня трансакційних витрат.

In the article the essence and nature of transaction costs existence at the economic activities of enterprises have been considered, the approaches that explain the nature of their origin are given. The transaction costs interpretations that have been developed within neoinstitutional theory to establish the research distribution on the macro and micro levels have been analyzed. An important factor of the transaction costs appearance at the industrial goods production is the presence of the following characteristics: specificity of assets, the limited number of industrial goods producers and buyers, which causes the opportunistic behavior of contractors. Taking this factor into account the own definition of production activity transaction costs have been proposed. It is generalize results of existing definitions of transaction costs with specifying the conditions of their occurrence, and provides exact identification of the production activity transaction costs in the total aggregate costs. The necessity of transaction costs optimizing to increase the economic activity efficiency of industrial enterprises has been grounded.
Management of industrial enterprises development in the context of transaction costs reducing
Keywords: розвиток економічного середовища; трансформаційні витрати; фактори середовища підприємства; професійні кадри; industrial enterprise; transaction costs; transformation costs; coaching; moderation